LISINOPRIL IMPLICATION IN THE CLINICAL PRACTICE - V. I. Podzolkov; A. I. Tarzimanova (Рациональная фармакотерапия в кардиологии)
The most socially significant cardiovascular diseases are recently considered from the standpoint of "cardiovascular continuum". Changes in neurohumoral factors especially activation of the renin-angiotensin-aldosterone system (RAAS) play a key role in the pathogenesis of the cardiovascular continuum. The first drugs that block RAAS were ACE inhibitors. Lisinopril deserves special attention among the ACE inhibitors. Lisinopril — one of the most known and well-studied drugs in this group with proven organoprotective properties. This allows its use in various clinical situations. Lisinopril is used for hypertension treatment long ago and there are a lot of evidences of its high antihypertensive efficacy currently. Lisinopril provides organ protection in various stages of the cardiovascular continuum and improves the life prognosis in patients with ischemic heart disease and chronic heart failure.